Fabrication of a biomimetic folded biostructure through controlled swelling of hydrogel - Ho, Ryan Jean Wei (Nanyang Technological University, 2024)
The intricate structures of organs, such as rugae and villi, are vital for their functionality in vertebrate organisms, including humans, yet they are prone to damage and failure. Organ donation remains a crucial but limited solution due to a global shortage of donors. Bioprinting, a promising approach within tissue engineering, offers a potential alternative by addressing challenges associated with organ damage. However, current bioprinting techniques struggle to replicate the complex architecture of natural tissues, highlighting the need for advancements in resolution and biocompatibility to cultivate diverse cell types effectively. In this study, we investigate the fabrication of a biomimetic folded biostructure using controlled swelling of hydrogel. The objective was to mimic the intricate folding mechanisms observed in natural tissues such as the gut and brain. We employed a combination of 3D bioprinting and casting methodologies to create hydrogel bilayers with varying concentrations of GelMA, a commonly used bioink. The mechanical properties of GelMA-based hydrogels, including compressive modulus and swelling ratio, were carefully controlled by adjusting parameters such as the degree of methacryloyl substitution and polymer concentration. We observed that higher GelMA concentrations led to increased compressive modulus and decreased swelling ratio, resulting in more regular deformation behaviour during swelling. Our findings suggest that precise control over hydrogel properties and printing parameters is essential for achieving desired wrinkle patterns in biomimetic structures. Future research directions include exploring alternative biomaterials, optimizing bioprinting techniques, investigating the impact of thickness ratio and the geometry of the physical constraint or mold used during the swelling process on the deformation on wrinkle formation. Overall, this study contributes to the development of advanced fabrication methods for biomimetic tissue engineering applications.